Cutaneous Transmissible Venereal Tumour in a 3-Month Old Pup: A Rare Case - Gupta, Surbhi; Kataria, Deepika; Chabra, Sushma; Preet, Gurpreet Singh; Gupta, Kuldip (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Canine sticker cell or cell tumor or Canine transmissible venereal tumour (TVT) is a contagious naturally occurring, round cell tumour of dogs with a global prevalence of 0.5-10 % (Strakova and Murchison, 2014). The disease is spread directly between dogs by copulation-induced vaginal abrasions, and is most frequently linked to irresponsible breeding practices or a lack of adequate veterinary services (Das and Das, 2000). Additionally biting, clawing, sniffing and licking has also been linked to direct transmission (Marcos et al., 2006). It is mostly found on genitalia but can be found on other parts and cutaneous also (Goldschmidt, 2002) and is characterized by irregular, multi nodular to cauliflower- like ulcerated growth in genital or extra-genital areas (Jangir et al., 2019). In pediatric canines with immunosuppression, tumour implantation may be extensive and exhibit aggressive clinical behavior (such as rapid neoplastic development and metastasis) (Marcos et al., 2006; Stockmann et al., 2011). The disease has a very good prognosis with the right chemotherapy and supportive treatment (Preet et al., 2021). The case reported here is notable because it showed an unusual clinical presentation of multifocal cutaneous lesions of TVT with traditional diagnostic findings in a 3 month old pediatric puppy. In order to achieve the best possible patient outcomes, it is crucial to be aware of uncommon clinical presentations, be aware of your diagnostic alternatives, and be familiar with the typical diagnostic findings of TVT. Early diagnosis in this case was made possible by cytology, which was later confirmed by histology.